2020
DOI: 10.3168/jds.2020-18232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding a palmitic acid–enriched supplement on production responses and nitrogen metabolism of mid-lactating Holstein and Jersey cows

Abstract: This study evaluated the effect of feeding a palmitic acid-enriched supplement on production responses and nitrogen metabolism of mid-lactating Holstein and Jersey cows. Eighty mid-lactating dairy cows, 40 Holstein and 40 Jersey, were used in a randomized complete block design with a split-plot arrangement; the main plot was breed and the subplot was fatty acid treatment. Cows within each breed were assigned to 1 of 2 treatments:(1) control diet with no fat supplement or (2) control diet plus a palmitic acid-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…Palmitic acid is the major FA in CSPF and is an important component in the biomembrane of fibrolytic bacteria (Mackie et al, 1991;Vlaeminck et al, 2006). Several studies have demonstrated that C16:0 supplementation increases NDF digestibility (e.g., de Souza et al, 2018;Sears et al, 2020). Therefore, it is possible that CSPF increased NDF digestibility by a combination of both factors: the reduction of DMI and the effect of C16:0 on fibrolytic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Palmitic acid is the major FA in CSPF and is an important component in the biomembrane of fibrolytic bacteria (Mackie et al, 1991;Vlaeminck et al, 2006). Several studies have demonstrated that C16:0 supplementation increases NDF digestibility (e.g., de Souza et al, 2018;Sears et al, 2020). Therefore, it is possible that CSPF increased NDF digestibility by a combination of both factors: the reduction of DMI and the effect of C16:0 on fibrolytic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Feed conversion ratio was calculated as previously described ( Sears et al, 2020 ) using the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…A maioria dos estudos se reporta a vacas leiteiras da raça Holandês, porém a raça Jersey é a segunda mais popular nos Estados Unidos (USDA -NAHMS, 2014), caracterizadas por menor produção de leite com maiores porcentagens de gordura e proteína em comparação com outras raças leiteiras cosmopolitas (ROVEGLIA et al, 2019). Bovinos leiteiros da raça Holandês, além de apresentarem maior tamanho corporal, produzem maior quantidade de leite, mas com menor concentração de gordura, o que sugere um diferente mecanismo de regulação da gordura (SEARS et al, 2020).…”
Section: Apresentaçãounclassified